Design and Synthesis of Novel Thioureas Derived from 4‐(4‐Fluorophenoxy)aniline as Anticancer Agents. Issue 3 (1st February 2017) - Yıldız, İnci Nejla; Oruç‐Emre, Emine Elçin; Taşdemir, Demet; Karaküçük‐İyidoğan, Ayşegül; Ulaşlı, Mustafa; Bayram, Hasan
Abstract : A new series of thiourea derivatives were obtained by the reaction of 4‐(4‐fluorophenoxy) aniline with different isothiocyanates. Their chemical structures were confirmed by ultraviolet (UV), infrared (IR), nuclear magnetic resonance (NMR), and mass spectral data and elemental analysis. All the synthesized thiourea derivatives were evaluated for their in vitro cancer activity against the human breast cancer cell lines MCF‐7 (human breast adenocarcinoma) and SKBr‐3 (human epithelial breast adenocarcinoma). Most of the derivatives exhibited significant anticancer activity. Especially, compound3 showed the most potent activity (IC50 20.1 μM) against SKBr‐3 when compared with the drugs 5‐fluorouracil and cisplatin, and, most importantly, it did not affect normal breast epithelial cells (4010). Abstract : In this work, a new series of thiourea derivatives were obtained by the reaction of 4‐(4‐flourophenoxy)aniline with different isothiocyanates. The compounds3, 7, 8, 9, 10, 12, 13, 15, and17 showed excellent activity compared to reference drugs on MCF‐7 and SKBR3 cell lines. Especially, compound3 did not show any cytotoxic effect on the normal breast cell line.